Penyuluhan Gizi Balita dan Demonstrasi Memasak MP-ASI di Desa Dramaga, Bogor - Ramadhani, Nawangsari; Abdillah, Muhammad Naabil; Mandhegani, Muhammad; Larasati, Afriliani Tasya; Zahrah, Aulia; Albab, Sidik Ullul; Salwa, Nurfikah; Nurhidayat, Agung Sahrul; Suryani, Andi Lisna; Hakim, Mochammad Za’im; Krisnatuti, Diah (Jurnal Pusat Inovasi Masyarakat, 2024)
An increase in the number of children under the stunting category has become a challenge for Dramaga Village. One of the factors causing such an increase is the shortage and lack of public awareness and education regarding practices to prevent stunting, one of which involves providing sufficient nutrition in children under two years of age. Stunting in children can prove detrimental in later years as it in hibits both physical and mental development in children. Intervention in the form of a workshop with cooking demonstration for expectant mothers and mothers with toddlers serves to increase public awareness and understanding about appropriate practices to prevent stunting. All participants indicated moderate to high satisfaction towards the event whether from the speaker or from the cooking demonstration conducted. Pre-test results indicated that participants already possessed an adequate understanding of the material presented with an overall pre-test average of 94,4%. Participant understanding did not have a significant increase based on a t-test evaluation, however, materials presented in a lecture setting with visual aid and a cooking demonstration may be a more interesting method of presentation and socialization for participants.